A comparison of ICD-11 and DSM-5 criteria of PTSD among Chinese trauma-exposed adolescent samples - Wang, Li; Fang, Ruojiao; Chen, Chen; Cao, Chengqi (Frontiers in Psychiatry, 2023)
This study aimed at comparing the prevalence and comorbidity differences of PTSD according to ICD-11 and DSM-5 definition across two Chinese adolescent trauma-exposed samples. A total of 1201 students exposed to earthquake and 559 students from vocational schools were included in this study. The PTSD Checklist for DSM-5 were used to measure PTSD symptoms. The MDD and GAD subscales of the Revised Children’s Anxiety and Depression Scale were used to measure major depression disorder (MDD) and generalized anxiety disorder (GAD) symptoms. No significant PTSD prevalence differences between ICD-11 and DSM-5 were found across the two samples. The differences regarding comorbidities between ICD-11 and DSM-5 definition were not significant among these two samples. The results revealed that the ICD-11 and DSM-5 provided similar prevalence of PTSD and comorbidity rates with MDD and GAD. This study carries implications for understanding the nature of the nature of the definition of PTSD and adds to knowledge about organizing and application of these two global applied criteria of PTSD.